Investigation of Solar Refrigeration System with Ground Based Cold Thermal Energy Storage for Tropical Countries - Zamberi, Mohd Zaim Zarin (IRC, 2021)
Solar energy is one of the most promising renewable energy that aligns with the current worldwide energy trends towards using renewable energy to complement current energy production for general consumption.